Psychological activity in sport (1997)
This third issue of volume 3 of Coaching Science Abstracts focuses on a general framework of thinking that is associated with superior training and competitive performances. The latter sections involve three popular methods for analyzing the appropriateness of thinking and psychological states. Topics: - COGNITIVE ACTIVITY, - AROUSAL, ANXIETY, AND STRESS, - MEASURING PSYCHOLOGICAL ACTIVITY.